Factors Affecting Teachers’ Pedagogical Adoption of ICT - Somekh, Bridget (International Handbook of Information Technology in Primary and Secondary Education, 2008)
this chapter uses insights from socio-cultural theory to develop a new analysis of the process of teachers’ pedagogical adoption of ICT. It refutes the common assumption that failure to embed ICT in pedagogy is the result of teachers’ resistance to change, and argues the need for a wider analytic frame that takes into account complex cultural factors and the regulatory frameworks and policies of national education systems. Humans learn to use new tools by, first, attempting to find a ‘fit’ with existing social practices and over time, through experimentation, developing new social practices that take advantage of their affordances. This process is always enabled or constrained by organisational structures, social contexts and established mechanisms of control, such as national curricula and assessment regimes. The chapter provides examples of transformative pedagogies with ICT and draws attention to the common factors which have enabled their success.
Keywords: Affordance; Change; Computers and Education; Education (general); Educational technology; Innovation; Learning & Instruction; Research partnerships; Socio-cultural theory; Teacher professional development; Transformative pedagogy